Design and control of a bidirectional interlinking converter for grid energy storage - Yang, Haoxin (2018)
This report aims to design two different types (analog and digital) of converter controllers for a flywheel energy storage system to realize bidirectional energy exchange between grid and flywheel. The system is based on a back to back converter structure. Firstly, Some background information about flywheel energy storage and its control strategies are introduced. In this project, a multiloop control arrangement would be used to realize the control of DC link voltage and flywheel rotate speed. The mathematical model of the flywheel energy storage system is derived in both natural coordinates and synchronization rotary coordinates. As for controller implementations, PI controllers are applied because the integral part can guarantee zero steady-state tracking error for DC signals. The controller parameters are calculated as required by setting time and damping ratio, and the control performances are tested via Simulink. Eventually, system transient state during bidirectional energy exchange period is analyzed. The theoretical calculation results we derived are compared with the simulation results via Simulink.